"My mama told me it would happen": menarche and menstruation experiences across generations. Issue 1 (2nd January 2020) - DeMaria, Andrea L.; Delay, Cara; Sundstrom, Beth; Wakefield, Audrey L.; Naoum, Zeina; Ramos-Ortiz, Jaziel; Meier, Stephanie; Brig, Kristin
ABSTRACT: The purpose of this study was to understand women's menarche and menstruation-related knowledge, attitudes, and behaviors across generations. Women ages 18 years and older (Mean = 49.13 ± 14.76 years; Range = 19–78 years) living in South Carolina were recruited to participate in semi-structured interviews during May-November 2016. A total of 70 interviews were conducted, which were audio-recorded and transcribed verbatim. Thematic analysis using open and axial coding techniques from grounded theory provided the framework for data interpretation. Women described vivid menarche memories; however, most women had not received proper education or preparation for what to expect prior to onset. Participants discussed their experiences with menstrual products, oral contraceptives, and medical procedures to suppress, manipulate, or manage menstruation. Findings provide practical recommendations for health professionals to develop further effective and timely messaging related to menarche and menstruation across the lifespan. Messaging should inform women about what to expect with menarche, menstruation management, and health-related impacts, as well as methods to reduce menses-related myths and stigmas.